Antidiabetic Activity of Catharsntus Pusillus: A Review - Asija, Rajesh; Swami, Amandeep; Hussain, Saddam (Journal of Biomedical and Pharmaceutical Research, 2023)
There are over 800 species of ficus, an evergreen tree in the Moraceae family. The entire plant, particularly the leaves of Ficus religiosa and Ficus benghalensis, has long been thought to aid in the healing of wounds. Additionally, the plant’s leaves are said to possess antibacterial, antioxidant, and anti-inflammatory qualities. This study assessed the ability of aqueous extracts of Ficus religiosa and Ficus benghalensis to heal wounds in rats by estimating biochemical parameters and utilizing the excision, incision, and dead space models. The breaking strength and the percentage of wound contraction or closure were assessed in the incision and excision wound models, respectively. The effectiveness of medications against the proliferative and remodeling phases of wound healing was assessed in the dead space model. In addition, GSH, Catalase and MDA estimation studies were employed to assess the efficacy of both the plants in vivo. The treatment of wound with ointment containing aqueous extracts of Ficus religiosa and Ficus benghalensis exhibited significant wound healing. The results were comparable to standard drug povidone iodine ointment, in terms of wound contraction, tensile strength and histopathological parameters. A significant antioxidant activity was observed as evidenced from decreased level of MDA and increased the level of GSH, catalase in extract treated animals as compared to control animals. Keywords: Ficus Religiosa, Remodeling, Biochemical, Catalase, MDA, GSH